A heat-activated coal gangue-based low-carbon cementitious material and a preparation method thereof

CN122916591APending Publication Date: 2026-10-16XIAN UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611255747.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为了弥补以上不足,因此,本发明提供一种热活化煤矸石基低碳胶凝材料及其制备方法,对煤矸石进行机械-热活化处理,显著提高了其比表面积和活性,解决了现有技术中煤矸石活性组分释放不充分的问题;同时通过严格控制煤矸石的化学成分、煅烧工艺参数以及混合工艺,实现了胶凝材料性能的稳定性和一致性,减少了力学性能的损失;本发明采用较低的煅烧温度,显著降低了生产能耗,且利用本方案凝胶材料制得的水泥胶砂具有优异的力学性能和施工性能,能够满足高效、低碳、绿色建筑材料的需求

Benefits of technology

[0038] 1. This invention significantly improves the specific surface area and activity of coal gangue through mechanical-thermal activation treatment, solving the problem of insufficient release of active components in coal gangue in the prior art; at the same time, by strictly controlling the chemical composition, calcination process parameters and mixing process of coal gangue, the stability and consistency of cementitious material properties are achieved, and the loss of mechanical properties is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916591A_ABST
    Figure CN122916591A_ABST
Patent Text Reader

Abstract

The present application relates to the field of building materials, in particular to a kind of hot activated coal gangue-based low-carbon cementitious material and its preparation method, which is composed of the following components by mass fraction: activated coal gangue 20~36 parts, Portland cement clinker 50~70 parts, limestone 5~15 parts, gypsum 5~7 parts;Among them, the aluminum-silicon mass ratio of the activated coal gangue is 0.45~0.5;The activated coal gangue has a porous surface structure, with a pore size of 5~20 μm, a specific surface area of ≥200 m 2 / g;The chemical composition of the coal gangue meets: SiO2≥55wt%, Al2O3≥25wt%, Fe2O3≤2wt%;The average particle size of the limestone particles is less than 75 μm.The present application solves the problem of insufficient release of active components in coal gangue in the prior art;At the same time, by strictly controlling the chemical composition of coal gangue, calcination process parameters and mixing process, the performance loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials, specifically to a thermally activated coal gangue-based low-carbon cementitious material and its preparation method. Background Technology

[0002] With the deepening development of the low-carbon and environmental protection concept, the preparation of cementitious materials from industrial solid waste has become an important research direction in the field of building materials. Coal gangue, as a major industrial solid waste, can not only reduce environmental pollution through resource utilization but also reduce carbon emissions in traditional cement production processes, resulting in significant economic and environmental benefits. However, the addition of coal gangue inevitably reduces various performance indicators of cementitious materials, especially mechanical properties. Existing coal gangue-based cementitious materials still have some shortcomings in performance optimization, preparation processes, and application effects, leading to excessive loss in mechanical properties compared to cementitious materials without added coal gangue, making it difficult to meet the demands of high-efficiency, low-carbon, and green building materials.

[0003] CN117069399B discloses a cementitious material based on coal gangue solid waste and its preparation method. Using limestone and coal gangue as main raw materials, the material is calcined and cooled at 1220℃~1280℃ to obtain an activator containing 8%~10% free calcium oxide. The mechanical properties of the cementitious material are improved by reacting the free calcium oxide with the active silica and alumina in the coal gangue, while simultaneously achieving a large-scale application of coal gangue (comprehensive utilization rate of 48%). However, this technical solution involves high energy consumption due to the high-temperature calcination (1220℃~1280℃) and demanding equipment requirements, increasing production costs. Furthermore, this solution does not perform thermal activation treatment on the coal gangue, resulting in low conversion efficiency of kaolinite in the coal gangue, which affects the overall performance and stability of the cementitious material.

[0004] CN115321849B discloses a low-carbon cementitious material composed of ferromanganese slag and limestone, and its application. The material is prepared by mixing ferromanganese slag, limestone, silicate cement clinker, gypsum, and spontaneously combusting coal gangue in a specific ratio. In this scheme, the silicate cement clinker content can be as low as 30%, significantly reducing carbon dioxide emissions and achieving good compressive strength (28-day compressive strength ≥ standard value 32.5 MPa). However, the spontaneously combusting coal gangue used in this scheme is not thermally activated, and its surface morphology and pore structure are not sufficiently optimized, resulting in incomplete release of the active components and limiting further improvement in the mechanical properties of the cementitious material. Furthermore, this scheme lacks detailed specifications for the chemical composition and pretreatment process of the coal gangue raw material, which may lead to significant fluctuations in material properties and affect the effectiveness of practical engineering applications.

[0005] The above problems indicate that existing coal gangue-based cementitious materials still have certain shortcomings in terms of thermal activation treatment of coal gangue, optimization of calcination process, control of raw material chemical composition, and improvement of mechanical properties. Summary of the Invention

[0006] To overcome the above shortcomings, this invention provides a thermally activated coal gangue-based low-carbon cementitious material and its preparation method. The mechanical-thermal activation treatment of coal gangue significantly improves its specific surface area and activity, solving the problem of insufficient release of active components in existing technologies. Simultaneously, by strictly controlling the chemical composition of the coal gangue, calcination process parameters, and mixing process, the stability and consistency of the cementitious material's performance are achieved, reducing the loss of mechanical properties. This invention uses a lower calcination temperature, significantly reducing production energy consumption. Furthermore, the cement mortar prepared using the gel material of this method exhibits excellent mechanical and construction properties, meeting the requirements for high-efficiency, low-carbon, and green building materials.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] This invention proposes a thermally activated coal gangue-based low-carbon cementitious material, composed of the following components in parts by weight:

[0009] 20-36 parts of activated coal gangue

[0010] 50-70 parts of silicate cement clinker

[0011] 5-15 parts limestone

[0012] 5-7 parts plaster;

[0013] The activated coal gangue has an aluminum-to-silicon mass ratio of 0.45 to 0.5; the activated coal gangue has a porous surface structure with a pore size of 5 to 20 μm and a specific surface area ≥ 200 m². 2 / g;

[0014] The chemical composition of the coal gangue satisfies: SiO2 ≥ 55wt%, Al2O3 ≥ 25wt%, Fe2O3 ≤ 2wt%;

[0015] The average particle size of the limestone particles is less than 75 μm.

[0016] After activation (such as thermal activation or mechanical activation), the internal mineral structure of coal gangue, including kaolinite, undergoes a transformation. Thermally activated coal gangue powder forms highly active amorphous metakaolinite and aluminosilicate amorphous phases. Under alkaline activation conditions, its active components, free SiO2 and Al2O3, combine with calcium ions in the system through the pozzolanic effect, ultimately forming a gelled product with CSH gel as the main phase and CAH as the secondary phase. The calcium hydroxide absorption method indirectly reflects the reactivity of the active substances by measuring the amount of calcium hydroxide absorbed by the coal gangue. These chemical composition limitations are designed to ensure that the coal gangue can undergo sufficient phase transformation during subsequent calcination to generate metakaolinite and enhance its activity. In the pretreatment stage, the coal gangue needs to undergo two processes: crushing and grinding.

[0017] Limestone powder exhibits both filling and nucleation effects. Limestone particles smaller than 75 μm can fill the pores in cement paste, reducing porosity and thus improving the mechanical properties of cementitious materials. Furthermore, in the nucleation effect, limestone particles can act as a nucleation matrix for hydrated calcium silicate (CSH), lowering the nucleation barrier and promoting the uniform distribution of hydration products. Metakaolinite in activated coal gangue can react with calcium hydroxide and limestone to form aluminocarbonates, hemialuminocarbonates, and monoaluminocarbonates, which is beneficial for improving and developing their mechanical properties. The reaction formula is as follows:

[0018]

[0019] Preferably, the weight ratio of silicate cement clinker to gypsum is 10-14:1, the weight ratio of activated coal gangue to limestone is 2-4:1, and the proportion of silicate cement clinker to the total mass is not less than 50%.

[0020] As a preferred option, the silicate cement clinker comprises 50 parts, activated coal gangue comprises 33.75 parts, limestone comprises 11.25 parts, and gypsum comprises 5 parts.

[0021] As a preferred option, the silicate cement clinker comprises 60 parts, activated coal gangue comprises 28 parts, limestone comprises 7 parts, and gypsum comprises 5 parts.

[0022] The thermally activated coal gangue-based low-carbon cementitious material prepared by this method achieves high performance mainly through the coordinated composition and proportion of its components. Experiments revealed that adding only activated coal gangue leads to a decrease in the fluidity of the cementitious material during use, and this decrease in fluidity becomes more pronounced with increasing amounts of activated coal gangue. Adding an appropriate proportion of limestone alleviates this problem because limestone acts as a filler, filling the voids between cement particles and optimizing the particle size distribution. This filling effect reduces the porosity of the system, releasing more free water and thus improving the slurry's flow properties. However, adding limestone may lead to a decrease in mechanical properties, and experiments showed that the performance changes after adding limestone to thermally activated coal gangue varied with different proportions. The optimal proportion is the one that ensures the best balance between fluidity and mechanical properties.

[0023] This solution proposes a method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material, comprising the following steps:

[0024] Coal gangue pretreatment: Crush the coal gangue to 5-7mm, grind it to an average particle size ≤80μm, and dry it to a moisture content ≤1wt%;

[0025] Mechanical-thermal activation: The pulverized coal gangue is calcined at 600~800℃ for 1~3h, with a heating rate of 8~12℃ / min, and then air-cooled to room temperature;

[0026] Dry ball milling: Activated coal gangue, clinker, limestone and gypsum are mixed in proportion and then added to a dry ball mill (ball-to-material ratio 3:1~5:1, zirconia grinding balls, particle size 3~10mm). The mixture is then dry ball milled at a speed of 20~40r / min and a milling time of 10~30min to obtain thermally activated coal gangue-based low-carbon cementitious material.

[0027] The crushed coal gangue should have a particle size controlled within the range of 5-7 mm, and then be fed into a ball mill for grinding until the average particle size reaches ≤80 μm. Precise control of particle size distribution helps improve the uniformity of coal gangue during calcination, avoiding activity differences caused by excessively large or small particles. After grinding, the coal gangue is placed in a drying oven to dry its moisture content to ≤1 wt%, preventing moisture from affecting subsequent calcination processes.

[0028] After mechanical-thermal activation and calcination, the color of the coal gangue sample gradually changed from gray to pinkish-white. Analysis shows that this color change is mainly due to the combustion of carbon during calcination, and the oxidation of some iron oxides to form hematite, which changes the valence state of iron and turns the color reddish-brown. Therefore, the color becomes pinkish-flesh pink at higher temperatures. Simultaneously, when the temperature reaches 900℃, fine particles tend to agglomerate into small spherical particles. The reasons for this are twofold: firstly, the quartz in the coal gangue undergoes a phase transformation, leading to lattice rearrangement and particle adhesion; secondly, the dehydration of kaolinite in the coal gangue to form metakaolinite further loosens its structure and exacerbates particle aggregation. After adding coal gangue powder at different calcination temperatures, the absorbance of calcium hydroxide, under the same holding time, generally showed a trend of first increasing and then decreasing. At 700℃, the absorbance of calcium hydroxide was 579.66 mg, the highest among all groups. This is because kaolinite in coal gangue powder undergoes dehydroxylation at high calcination temperatures. Before a new stable phase forms, silicon and aluminum readily dissolve from the crystal. Simultaneously, interlayer hydrogen bonds in the kaolinite crystal structure break, removing structural water and transforming from an ordered, plate-like crystal structure to a disordered metakaolinite crystal structure. Numerous interlayer silicon and aluminum active sites are exposed, increasing the absorbance of calcium hydroxide and indirectly demonstrating the increased pozzolanic activity of coal gangue powder. When the calcination temperature exceeds 800℃, active Al₂O₃ and SiO₂ begin to react, transforming in large quantities into an inert mullite crystal structure, causing a sharp decrease in the absorbance of calcium hydroxide from 800℃ to 900℃. During calcination, hydroxyl groups within the kaolinite lattice are removed, gradually disintegrating the layered, ordered crystal structure and ultimately transforming into a metakaolinite phase with amorphous, non-crystalline characteristics. This mineral phase transformation lays the material structural foundation for the pozzolanic activity of coal gangue, fully verifying the crucial role of the calcination process in the reconstruction of the coal gangue crystal structure. After calcination, the sample surface became rough and porous, with a significantly enlarged pore size. This morphological transformation is mainly attributed to the combustion loss of carbonaceous combustibles during calcination, the removal of structural water and hydroxyl groups from kaolinite, ultimately leading to a significant increase in the microporous structure of the sample.

[0029] Dry ball milling is a process that uses the mechanical force of a ball mill to uniformly mix activated coal gangue, silicate cement clinker, calcite limestone, and gypsum dihydrate. The grinding balls inside the mill repeatedly collide with and shear the powder particles at high speeds. This breaks down agglomerates between components, ensuring thorough dispersion of the highly active metakaolinite in the activated coal gangue, the C3S / C2S minerals in the clinker, the calcite crystals in the limestone, and the calcium sulfate dihydrate in the gypsum, achieving micron-level uniform mixing and eliminating localized component segregation. Furthermore, the mechanical action between the grinding balls and the powder creates microcracks and defects on the particle surface, increasing the specific surface area of ​​the powder and expanding the reaction interface with the hydration products. This enhances the dissolution and secondary hydration of the pozzolanic active components in subsequent hydration reactions, while avoiding incomplete hydration caused by powder agglomeration.

[0030] Preferably, after mixing in a dry ball mill, the average particle size of the thermally activated coal gangue-based low-carbon cementitious material is 45-60 μm.

[0031] Preferably, the particle size distribution D of the ground coal gangue is... 90 ≤150μm.

[0032] Preferably, the calcination heating rate is 8~12℃ / min, the calcination temperature is 650~720℃, and the holding time is 1.8~2.2h.

[0033] Preferably, the oxygen volume content in the atmosphere during calcination is 20% to 24%.

[0034] This is because coal gangue contains organic matter, and sufficient oxygen is needed to remove it completely.

[0035] Preferably, 0.1% to 0.3 wt% of a polycarboxylate superplasticizer (PCA) is added during the dry ball milling process to improve the dispersion uniformity.

[0036] To further improve the dispersibility of the mixture, 0.1% to 0.3 wt% of a polycarboxylate superplasticizer (PCA) can be added during the dry ball milling process. The addition of PCA can effectively prevent agglomeration, thereby improving the uniformity and mechanical properties of the cementitious material.

[0037] Compared with existing technologies, the advantages of this invention are:

[0038] 1. This invention significantly improves the specific surface area and activity of coal gangue through mechanical-thermal activation treatment, solving the problem of insufficient release of active components in coal gangue in the prior art; at the same time, by strictly controlling the chemical composition, calcination process parameters and mixing process of coal gangue, the stability and consistency of cementitious material properties are achieved, and the loss of mechanical properties is reduced.

[0039] 2. This invention uses a lower calcination temperature, which significantly reduces production energy consumption. Furthermore, the cement mortar made using the gel material of this method has excellent mechanical and construction properties, which can meet the needs of high-efficiency, low-carbon, and green building materials, and provides a new way for the resource utilization of industrial solid waste. Attached Figure Description

[0040] Figure 1 The images show the microscopic morphology of the coal gangue used in the examples before and after calcination. (a) is the uncalcined raw coal gangue, (b) is a partial enlarged view of (a), (c) is the coal gangue after calcination at 700℃, and (d) is a partial enlarged view of (c).

[0041] Figure 2The images show the spectra of the coal gangue used in the examples before calcination and after calcination at different temperatures.

[0042] Figure 3 The flowability test results of the cementitious material without limestone were used to verify the experimental process. The figure is numbered MC, where C represents the total mass percentage of activated coal gangue and limestone added.

[0043] Figure 4 The figure shows the flowability test results of cementitious materials with added limestone during the experimental verification process. The figure is numbered MC-a:b, where C represents the total mass ratio of activated coal gangue and limestone, and a:b is the ratio of the mass of activated coal gangue to the mass of limestone added.

[0044] Figure 5 The images show the XRD patterns of the coal gangue used in the examples before calcination and after calcination at different temperatures.

[0045] Figure 6 The images show the color changes of the coal gangue used in the examples before calcination and during calcination and heat preservation at different temperatures. Detailed Implementation

[0046] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0047] The main chemical components of the raw coal gangue used in this embodiment are SiO2, Al2O3, and small amounts of Fe2O3 and TiO2. The composition range is shown in Table 1.

[0048]

[0049] The silicate cement clinker used in the embodiments and comparative examples of this scheme is from Zhucheng Jiuqi Building Materials Co., Ltd., Shandong Province. The chemical composition and mineral composition of the clinker are shown in Tables 2 and 3, respectively. The particle size is 80μm and the specific surface area is 359m². 2 / kg, without the addition of coal gangue, after 28 days of curing, the compressive strength is 4.3MPa and the flexural strength is 6.8MPa.

[0050]

[0051]

[0052] General Implementation Examples

[0053] A method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material includes the following steps:

[0054] Coal gangue pretreatment: Crush the coal gangue to 5-7mm, grind it to an average particle size ≤80μm, D 90 ≤150μm, dried to a moisture content ≤1wt%; the chemical composition of coal gangue meets the following requirements: SiO2≥55wt%, Al2O3≥25wt%, Fe2O3≤2wt%, Loss≥18wt%;

[0055] Mechanical-thermal activation: The pulverized coal gangue is calcined at 600-800℃ for 1-3 hours with a heating rate of 8-12℃ / min, and then air-cooled to room temperature; the oxygen volume content in the atmosphere is 20%-24%;

[0056] Dry ball milling: After mixing activated coal gangue, silicate cement clinker, limestone, and dihydrate gypsum in a certain proportion, 0.1% to 0.3 wt% of polycarboxylate-based high-efficiency water-reducing agent can be added to the mixture. The mixture is then added to a dry ball mill with a ball-to-material ratio of 3:1 to 5:1, using zirconia grinding balls with a particle size of 3 to 10 mm. The mixture is dry ball milled at a speed of 20 to 40 r / min and a milling time of 10 to 30 min to obtain thermally activated coal gangue-based low-carbon cementitious material with an average particle size of 45 to 60 μm.

[0057] Figure 1 The images show the microstructure of the coal gangue used in this embodiment before and after calcination, divided into four parts: (a) is the uncalcined raw coal gangue; (b) is a magnified view of (a); (c) is the coal gangue after calcination at 700℃; and (d) is a magnified view of (c). Figure 1 It can be seen that after calcination at 700℃, the surface of (d) is significantly rougher than that of (b);

[0058] Figure 2 The images show the spectra of the coal gangue used in this embodiment after calcination at different temperatures. It can be seen that the uncalcined raw coal gangue (RCG) has a wavelength of 3696 cm⁻¹. -1 and 3619cm -1 The intensity of the hydroxyl characteristic peak at the calcination temperature is relatively high, and it weakens significantly after calcination at 600℃, indicating that some hydroxyl groups have been removed at this temperature. When the calcination temperature is raised to 700℃, these two absorption peaks disappear completely, directly reflecting the complete change in the crystal structure of kaolinite.

[0059] Figure 3 The figure shows the flowability test results of the cementitious material without limestone added during the experimental verification process (numbered MC, where C represents the mass percentage of activated coal gangue added). As can be seen from the figure, the flowability decreases as the amount of activated coal gangue added increases. Figure 4The results of the fluidity test of cementitious materials with added limestone (number MC-a:b, where C represents the total mass ratio of activated coal gangue and limestone, and a:b is the ratio of the mass of activated coal gangue to the mass of limestone added) show that adding a certain amount of limestone can inhibit the decrease in fluidity, and the optimal addition amount is a:b=4:1.

[0060] Figure 5 The images show the XRD patterns of the coal gangue used in the examples before calcination and at different temperatures. The characteristic diffraction peaks of the quartz phase remain relatively stable during the calcination process, with only slight fluctuations in peak intensity at different diffraction angles. In uncalcined coal gangue, the XRD pattern of the kaolinite phase exhibits sharp diffraction peaks with narrow half-peak widths. The intensity of the characteristic diffraction peaks of the (001) crystal plane (2θ=12.33°), (110) crystal plane (2θ=20.32°), and (111) crystal plane (2θ=21.45°) of kaolinite decreases significantly with the calcination process until they disappear completely, indicating that the kaolinite crystal structure undergoes a phase transition. According to the peak shape evolution law and peak position shift characteristics, this phenomenon is due to the removal of hydroxyl groups in the kaolinite lattice during the calcination process, which gradually disintegrates the layered ordered crystal structure and eventually transforms into a meta-kaolinite phase with amorphous and non-crystalline characteristics. This mineral phase transformation lays the material structure basis for the volcanic ash activity of coal gangue, fully verifying the key role of the calcination process in the reconstruction of the coal gangue crystal structure.

[0061] Figure 6 The color changes of coal gangue used in the examples before calcination and at different temperatures during calcination and heat preservation are shown in the image. Using black cardstock as the background, the samples were placed in sequence. It was found that as the calcination temperature and heat preservation time increased, the color of the coal gangue gradually changed from gray to pinkish-white after calcination. This change is mainly due to the burning of carbon in the coal gangue during the calcination process. Simultaneously, some iron oxides are oxidized under these conditions to form hematite, causing a change in the valence state of iron and a change in color to reddish-brown. Therefore, the color is pinkish-flesh at higher temperatures. Furthermore, when the temperature reaches 900℃, fine particles easily agglomerate, becoming small spherical particles. The reasons for this are twofold: first, the quartz in the coal gangue undergoes a phase transformation, leading to lattice rearrangement and particle adhesion; second, the dehydration of kaolinite in the coal gangue to form metakaolinite further loosens its structure, exacerbating particle aggregation.

[0062] Example 1

[0063] A method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material includes the following steps:

[0064] Coal gangue pretreatment: The coal gangue is crushed to 5mm, ground to an average particle size of 75μm, and dried to a moisture content of 0.8wt%; the chemical composition of the coal gangue meets the following requirements: SiO2=58.34wt%, Al2O3=28.25wt%, Fe2O3=1.73wt%, Loss=18.98wt%; D 90 =145μm;

[0065] Mechanical-thermal activation: The pulverized coal gangue was calcined at 700℃ for 2 hours with a heating rate of 10℃ / min and an oxygen volume content of 22% in the calcination atmosphere, and then air-cooled to room temperature.

[0066] Dry ball milling: 60 parts of silicate cement clinker, 28 parts of activated coal gangue, 7 parts of limestone with an average particle size of 70μm, and 5 parts of limestone dihydrate gypsum were mixed in proportion. Then, 0.2wt% of polycarboxylate-based high-efficiency water-reducing agent was added to the mixture. The mixture was then added to a dry ball mill with a ball-to-material ratio of 4:1. The mixture was dry ball milled at a speed of 30r / min and a milling time of 20min to obtain a thermally activated coal gangue-based low-carbon cementitious material with an average particle size of 55μm.

[0067] Example 2

[0068] A method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material includes the following steps:

[0069] Coal gangue pretreatment: The coal gangue is crushed to 5mm and ground to an average particle size of 74μm. 90 The particle size is 140 μm, and the material is dried to a moisture content of 0.8 wt%. The chemical composition of the coal gangue is as follows: SiO2 57.35 wt%, Al2O3 27.89 wt%, Fe2O3 1.76 wt%.

[0070] Mechanical-thermal activation: The pulverized coal gangue was calcined at 650℃ for 3 hours with a heating rate of 8℃ / min, and then air-cooled to room temperature; the oxygen volume content in the atmosphere was 20%.

[0071] Dry ball milling: 60 parts of silicate cement clinker, 28 parts of activated coal gangue, 7 parts of limestone with an average particle size of 70 μm, and 5 parts of gypsum dihydrate were mixed in proportion. Then, 0.1 wt% of polycarboxylate-based high-efficiency water-reducing agent was added to the mixture. The mixture was then added to a dry ball mill with a ball-to-material ratio of 4:1, using zirconia grinding balls with a particle size of 8 mm. The mixture was dry ball milled at a speed of 30 r / min for 30 min to obtain a thermally activated coal gangue-based low-carbon cementitious material with an average particle size of 53 μm.

[0072] Example 3

[0073] A method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material includes the following steps:

[0074] Coal gangue pretreatment: The coal gangue is crushed to 7mm and ground to an average particle size of 72μm. 90 =140μm, dried to a moisture content of 1.0wt%; the chemical composition of the coal gangue meets the following requirements: SiO2=58.14wt%, Al2O3=28.55wt%, Fe2O3=1.78wt%, Loss=18.53wt%;

[0075] Mechanical-thermal activation: The pulverized coal gangue was calcined at 750℃ for 1.5h with a heating rate of 12℃ / min, and then air-cooled to room temperature;

[0076] Dry ball milling: 60 parts of silicate cement clinker, 28 parts of activated coal gangue, 7 parts of limestone with an average particle size of 70 μm, and 5 parts of dihydrate gypsum were mixed in proportion and then added to a dry ball mill with a ball-to-material ratio of 3:1 and a zirconia grinding ball particle size of 4 mm. The mixture was dry ball milled at a speed of 25 r / min for 15 min. 0.15 wt% of polycarboxylate-based high-efficiency water-reducing agent was added to the mixture to obtain a thermally activated coal gangue-based low-carbon cementitious material with an average particle size of 58 μm.

[0077] Example 4

[0078] A method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material includes the following steps:

[0079] Coal gangue pretreatment: The coal gangue is crushed to 5mm, ground to an average particle size of 74μm, and dried to a moisture content of 0.8wt%; the chemical composition of the coal gangue meets the following requirements: SiO2=58.34wt%, Al2O3=28.25wt%, Fe2O3=1.73wt%, Loss=18.98wt%; D 90 =145μm;

[0080] Mechanical-thermal activation: The pulverized coal gangue was calcined at 700℃ for 2 hours with a heating rate of 10℃ / min and an oxygen volume content of 22% in the calcination atmosphere, and then air-cooled to room temperature.

[0081] Dry ball milling: 50 parts of silicate cement clinker, 33.75 parts of activated coal gangue, 11.25 parts of limestone with an average particle size of 70 μm, and 5 parts of limestone dihydrate gypsum were mixed in proportion. Then, 0.2 wt% of polycarboxylate-based high-efficiency water-reducing agent was added to the mixture. The mixture was then added to a dry ball mill with a ball-to-material ratio of 4:1 and dry ball milled at a speed of 30 r / min for 20 min to obtain a thermally activated coal gangue-based low-carbon cementitious material with an average particle size of 55 μm.

[0082] Example 5

[0083] A method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material includes the following steps:

[0084] Coal gangue pretreatment: The coal gangue is crushed to 5mm, ground to an average particle size of 75μm, and dried to a moisture content of 0.8wt%; the chemical composition of the coal gangue meets the following requirements: SiO2=58.34wt%, Al2O3=28.25wt%, Fe2O3=1.73wt%, Loss=18.98wt%; D 90 =145μm;

[0085] Mechanical-thermal activation: The pulverized coal gangue was calcined at 700℃ for 2 hours with a heating rate of 10℃ / min and an oxygen volume content of 22% in the calcination atmosphere, and then air-cooled to room temperature.

[0086] Dry ball milling: 70 parts of silicate cement clinker, 20 parts of activated coal gangue, 5 parts of limestone with an average particle size of 70μm, and 5 parts of gypsum dihydrate were mixed in proportion. Then, 0.25wt% of polycarboxylate-based high-efficiency water-reducing agent was added to the mixture. The mixture was then added to a dry ball mill with a ball-to-material ratio of 4:1. The mixture was dry ball milled at a speed of 30r / min and a milling time of 30min to obtain a thermally activated coal gangue-based low-carbon cementitious material with an average particle size of 52μm.

[0087] Example 6

[0088] A method for preparing the above-mentioned thermally activated coal gangue-based low-carbon cementitious material includes the following steps:

[0089] Coal gangue pretreatment: The coal gangue is crushed to 5mm, ground to an average particle size of 75μm, and dried to a moisture content of 0.8wt%; the chemical composition of the coal gangue meets the following requirements: SiO2=58.34wt%, Al2O3=28.25wt%, Fe2O3=1.73wt%, Loss=18.98wt%; D 90 =145μm;

[0090] Mechanical-thermal activation: The pulverized coal gangue was calcined at 700℃ for 2 hours with a heating rate of 10℃ / min and an oxygen volume content of 22% in the calcination atmosphere, and then air-cooled to room temperature.

[0091] Dry ball milling: 50 parts of silicate cement clinker, 35 parts of activated coal gangue, 8 parts of limestone with an average particle size of 70 μm, and 7 parts of limestone dihydrate gypsum were mixed in proportion and then added to a dry ball mill with a ball-to-material ratio of 4:1. The mixture was dry ball milled at a speed of 30 r / min for 20 min to obtain a thermally activated coal gangue-based low-carbon cementitious material with an average particle size of 56 μm.

[0092] Comparative Example 1

[0093] The difference from Example 1 is that it exceeds the upper limit, which is Fe2O3 = 2.1wt%.

[0094] Comparative Example 2

[0095] The difference from Example 1 is that after grinding, it is dried to a moisture content of 1.5 wt%.

[0096] Comparative Example 3

[0097] The difference from Example 1 is that the pulverized coal gangue was used directly without calcination.

[0098] Comparative Example 4

[0099] The difference from Example 1 is that the ground coal gangue was calcined at 850°C for 2 hours.

[0100] Comparative Example 5

[0101] The difference from Example 1 is that the ground coal gangue was calcined at 500°C for 2 hours.

[0102] Comparative Example 6

[0103] The difference from Example 1 is that the calcination heating rate after grinding is 15℃ / min.

[0104] Comparative Example 7

[0105] The difference from Example 1 is that SiO2=59wt%, Al2O3=26wt%, and the aluminum-silicon ratio is 0.44.

[0106] Comparative Example 8

[0107] The difference from Example 1 is that limestone was not added, but 35 parts of activated coal gangue were added.

[0108] Comparative Example 9

[0109] The difference from Example 1 is that the mixture was not mixed by dry ball milling.

[0110] Comparative Example 10

[0111] The difference from Example 1 is that the average particle size of the limestone is 85 μm.

[0112] Comparative Example 11

[0113] The difference from Example 1 is that the weight ratio of activated coal gangue to limestone is 5:1, that is, 29 parts of activated coal gangue and 6 parts of limestone.

[0114] Comparative Example 12

[0115] The difference from Example 1 is that 40 parts of activated coal gangue, 40 parts of silicate cement clinker, 15 parts of limestone, and 5 parts of gypsum are used.

[0116] Comparative Example 13

[0117] The difference from Example 1 is that the oxygen concentration is too low, at 19%, and the loss on ignition is 18.2%.

[0118] Performance testing:

[0119] Referring to GB / T17671-2021, the thermally activated coal gangue-based low-carbon cementitious material samples prepared in Examples 1-5 and Comparative Examples 1-12 were used to prepare cement mortar samples for testing:

[0120] (1) Weigh the required number of samples for each group using a 1% balance, label each sample separately in a plastic bag, and mix them together when used later;

[0121] (2) Cement test blocks were prepared using a cement mortar mixer. 225 ml of distilled water was poured into the pot, followed by the first step of mixing the sample. The pot was then fixed on the stand and raised to the working position. The mixture was stirred at low speed for 30 seconds. In the second 30 seconds, 1350 g of standard sand was added evenly. Then, the mixture was stirred at high speed for 30 seconds to mix the standard sand and the sample evenly. The mixing was stopped for 90 seconds. The mortar on the mixer blades, pot walls, and bottom was scraped into the pot with a scraper. The mixture was then stirred at high speed for another 60 seconds to finish.

[0122] (3) Molding should be carried out immediately after the mortar is prepared. The cleaned and oiled empty mold and mold sleeve are fixed on the vibration table. The mortar on the pot wall is cleaned into the pot with a scraper and the mortar in the pot is manually stirred with a scraper to make it more uniform. When molding, the mortar is filled into the mold in two layers. The first layer is filled into the mold to two-thirds full and smoothed with a scraper. Then it is vibrated 60 times. The second layer of mortar is filled in. The remaining material is gently scraped into the mold with a scraper. The scraper should not touch the first layer of vibrated mortar. The surface is smoothed with a scraper and then vibrated 60 times. Each time it is vibrated, a piece of cotton gauze that has been wetted and wrung out and is slightly larger than the size of the mold sleeve can be placed on the mold sleeve to prevent the mortar from splashing during vibration. Remove the mold sleeve and take the mold off the vibration table. Use a metal ruler to slowly move along the length of the mold with a horizontal sawing motion to the other end to scrape off the mortar that exceeds the part of the mold. The number of smoothing times should be as small as possible. The total number of times should not exceed 3. Finally, wipe away any slag around the mold. Label each group with its number.

[0123] (3) After the prepared sample is left to stand for 24 hours, it is then demolded using a rubber mallet. The marked specimen is placed horizontally (with the scraped side facing up) in water at 20°C for curing, ensuring that the water is in contact with all six sides of the specimen. Curing is carried out until the required age is reached, during which 30% of the water is replaced every week.

[0124] Performance testing: Cement mortar strength is tested according to GB / T17671-2021, setting time and standard consistency water consumption of cementitious materials are tested according to GB / T1346-2011, and flowability of cement mortar is tested according to GB / T2419-2005.

[0125] Performance tests are shown in Table 4, where the control group is the silicate cement clinker group without added coal gangue and limestone:

[0126]

[0127] Experimental data show that adding coal gangue as an industrial solid waste substitute for part of silicate cement clinker can indeed lead to a decrease in the mechanical properties of cementitious materials due to the reduced clinker content. This invention reduces this performance loss by optimizing the composition and process. The 28-day compressive strength of the control group without added coal gangue and limestone was 4.3 MPa. In Examples 1-6, after adding a combination of activated coal gangue and limestone, the 28-day compressive strength was still maintained at a relatively high level of over 41.0 MPa. This indicates that the performance loss caused by the introduction of coal gangue was effectively reduced through mechanical thermal activation treatment and component synergy. In the embodiments, coal gangue is calcined at 600 to 800°C to transform into highly active metakaolinite. Its porous structure and high specific surface area enhance its reactivity with calcium ions in clinker, generating more CSH gel and other cementing products, which compensates for the strength loss caused by the reduction of clinker due to the substitution of coal gangue. The filling effect of limestone with an average particle size of less than 75 μm further reduces the porosity of the slurry, helps maintain strength, and improves the fluidity of the embodiment, avoiding the slurry dryness problem that may be caused by simply adding coal gangue.

[0128] The performance changes in the comparative examples more intuitively reflect the significance of process optimization in reducing losses. Compared to Example 1, the performance degradation in each comparative example can be explained by deviations from these core designs:

[0129] Comparative Example 3, which was not calcined, retained its ordered kaolinite structure, with active sites remaining unexposed and unable to effectively participate in the pozzolanic reaction, resulting in the most significant performance loss. This directly confirms that mechanical-thermal activation helps to further stimulate the activity of coal gangue. Comparative Examples 4 and 5, due to calcination temperatures deviating from 600-800℃, showed insufficient metakaolinite formation due to the conversion of active silica and aluminum to inert mullite at high temperatures in the former and incomplete dehydroxylation of kaolinite at low temperatures in the latter. This further illustrates the scientific validity of the calcination temperature range defined in this invention, ensuring complete kaolinite conversion while avoiding the formation of inert phases within this range.

[0130] Comparative Examples 1 and 7, due to deviations in the chemical composition of coal gangue from the specified range, excessive iron oxides, or unsuitable aluminum-silicon ratios, interfered with the synergistic reaction between the silicon-aluminum components and calcium, resulting in a non-dense structure of the cementitious products. This echoes the design logic of controlling the chemical composition of coal gangue in the invention to ensure sufficient phase transformation, proving that the precision of raw material composition is the foundation for orderly reaction. Comparative Examples 8 and 11, due to the lack of limestone or imbalance in proportion, lost the assistance of filling and nucleation effects, resulting in a loose slurry structure and uneven distribution of hydration products. This reflects the design significance of "optimizing the particle size distribution of limestone and promoting hydration" in the invention, that is, achieving synergy between activity activation and structural optimization through proportional coordination.

[0131] Comparative Example 12 suffered from insufficient clinker content and a lack of calcium source, failing to meet the calcium ion requirements of the volcanic ash reaction, resulting in insufficient formation of cementitious products. This is directly related to the invention's requirement that the clinker content be no less than 50%, indicating that a sufficient calcium source is a necessary condition for the activation of coal gangue. Comparative Examples 13 and 6 suffered from insufficient calcination oxygen concentration or excessively rapid heating rate. The former led to incomplete combustion of organic matter and residual carbonaceous material obscuring active sites, while the latter caused uneven thermal stress and inconsistent activation within the coal gangue. Both affected the quality of metakaolinite formation, confirming the value of the process design in the invention that controls the calcination atmosphere and heating rate to ensure uniform activation.

[0132] Comparative Example 9, due to the absence of dry ball milling, resulted in uneven mixing of components and incomplete local reactions, further verifying the necessity of the dry ball milling mixing process design in the invention for more uniform mixing.

Claims

1. A thermally activated coal gangue-based low-carbon cementitious material, characterized in that, It consists of the following components in parts by weight: 20-36 parts of activated coal gangue 50-70 parts of silicate cement clinker 5-15 parts limestone 5-7 parts plaster; The activated coal gangue has an aluminum-to-silicon mass ratio of 0.45 to 0.5; the activated coal gangue has a porous surface structure with a pore size of 5 to 20 μm and a specific surface area ≥ 200 m². 2 / g; The chemical composition of the coal gangue satisfies: SiO2 ≥ 55wt%, Al2O3 ≥ 25wt%, Fe2O3 ≤ 2wt%; The average particle size of the limestone particles is less than 75 μm.

2. The thermally activated coal gangue-based low-carbon cementitious material as described in claim 1, characterized in that, The weight ratio of silicate cement clinker to gypsum is 10-14:1, the weight ratio of activated coal gangue to limestone is 2-4:1, and the proportion of silicate cement clinker to the total mass is not less than 50%.

3. The thermally activated coal gangue-based low-carbon cementitious material as described in claim 1, characterized in that, The composition of the cement is as follows: 50 parts silicate cement clinker, 33.75 parts activated coal gangue, 11.25 parts limestone, and 5 parts gypsum.

4. The thermally activated coal gangue-based low-carbon cementitious material as described in claim 1, characterized in that, The composition of the cement is as follows: 60 parts silicate cement clinker, 28 parts activated coal gangue, 7 parts limestone, and 5 parts gypsum.

5. A method for preparing a thermally activated coal gangue-based low-carbon cementitious material as described in any one of claims 1-4, characterized in that, Includes the following steps: Coal gangue pretreatment: Crush the coal gangue to 5-7mm, grind it to an average particle size ≤80μm, and dry it to a moisture content ≤1wt%; Mechanical-thermal activation: The pulverized coal gangue is calcined at 600~800℃ for 1~3 hours and then air-cooled to room temperature; Dry ball milling: Activated coal gangue, clinker, limestone and gypsum are mixed in proportion and then added to a dry ball mill to obtain thermally activated coal gangue-based low-carbon cementitious material.

6. The method for preparing thermally activated coal gangue-based low-carbon cementitious material as described in claim 5, characterized in that, After mixing in a dry ball mill, the average particle size of the thermally activated coal gangue-based low-carbon cementitious material is 45-60 μm.

7. The method for preparing thermally activated coal gangue-based low-carbon cementitious material as described in claim 5, characterized in that, The particle size distribution D of the ground coal gangue 90 ≤150μm.

8. The method for preparing thermally activated coal gangue-based low-carbon cementitious material as described in claim 5, characterized in that, The calcination heating rate is 8~12℃ / min; the calcination temperature is 650~720℃, and the holding time is 1.8~2.2h.

9. The preparation method of the thermally activated coal gangue-based low-carbon cementitious material as described in claim 5, characterized in that, During the calcination process, the oxygen volume ratio in the atmosphere is 20% to 24%.

10. The method for preparing thermally activated coal gangue-based low-carbon cementitious material as described in claim 5, characterized in that, During the dry ball milling process, 0.1% to 0.3 wt% of a polycarboxylate-based high-efficiency water-reducing agent is added to the mixture.

Citation Information

Patent Citations

  • A low-carbon cementitious material composed of ferrosilicon slag and limestone and its application

    CN115321849B

  • A cementitious material based on coal gangue solid waste and a preparation method thereof

    CN117069399B